Combining store-and-forward pictures and videoconferencing for outpatient burn follow-up care. Issue 4 (October 2018) - Brownson, Elisha G.; Wong, Joshua; Cannon, Cathie; Thompson, Callie M.; Mandell, Samuel P.; Gibran, Nicole S.; Muffley, Lara; Pham, Tam N.
Highlights: BurnPics is a patient-centered program for follow-up burn care in a large regional catchment area. Follow-up care by videoconferencing saves significant times for patients and clinic staff. Direct telehealth care to the patient's home replaces the traditional hub-and-spoke care model. Abstract: Objective: Regional burn centers face challenges in follow-up care for large catchment areas. In 2006, we implemented a store-and-forward outpatient protocol ("BurnPics") for established burn patients in our region to assess healing and range of motion. Starting August 2014, we added videoconferencing visits for select patients. The purpose of this quality improvement project was to evaluate BurnPics and videoconferencing utilization. Methods: We reviewed records of patients enrolled in the BurnPics program from August 2014 through July 2015. We evaluated videoconferencing enrollment, provider time, and revenue generation. Data was analyzed using descriptive statistics. Results: There were 398 BurnPics patients. Most patients resided in-state (82%). Median distance from residence to burn center was 67 miles (IQR 29–228). Fifty-three patients underwent 85 videoconferencing visits; 30 visits (35%) were billable, 27 visits (32%) were post-operative follow-ups, and 28 visits (33%) were not billable due to out-of-state residence. Median time per video-visit was 46 min (IQR 35–60); median burn care provider time was 11 min (IQR 7–14). Conclusions: The BurnPics program has potential to mitigate challenges of follow-up burn care. Videoconferencing has improved our follow-up care and created minimal time burden on providers. Future legislative efforts will help minimize financial and legal barriers to successful regional telehealth programs.